PENGARUH SARI KACANG HIJAU TERHADAP KADAR HEMOGLOBIN IBU NIFAS - Desideria Yosepha Ginting; Layari Tarigan; Dwi Handayani (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2020)
Postpartum anemia is caused due to insufficient iron supplementation and excessive bleeding during or after delivery. The initial survey found that there were 5 mothers who had anemia. This study aims to determine the effect of mung bean juice on hemoglobin levels in postpartum mothers, by using quantitative research. The population in this study were all 12 postpartum mothers in the first week. The sampling technique used is total sampling. Data collection was done by using observation. The average Hb level before being given green bean juice was 12.74 gr / dL and after that was 12.75 gr / dL. The difference in mean Hb levels before and after giving green bean juice was 0.008 gr / dL. The results of statistical tests using paired sample t-test (CI: 95%) obtained Ï value of 0.972, so it can be concluded that there is no effect of mung bean juice on hemoglobin levels of postpartum mothers. For postpartum mothers to be more proactive in seeking information about anemia, as well as finding out the benefits of green bean juice.